Diversidade genética em populações de Campomanesia xanthocarpa Berg. oriundas de fragmentos da Mata Atlântica - Silva, Lucas Fernando da (2012)
Forest fragmentation is a reality in all forest biomes of the world. Among the Biomes more fragmented is Atlantic Forest. The species Campomanesia xanthocarpa Berg. (Myrtaceae) is native to the Atlantic Forest, fruit tree, with high ecological importance and potential in the cosmetics and food industry. Genetic studies to verify the effect of fragmentation on populations of this species are lacking. This study aimed to determine population-genetic parameters of three populations of C. xanthocarpa being an isolated population (A) and two connected by corridors of forest (B and C) and based on determined parameters, estimate the effect of fragmentation on populations under study. This study used six ISSR (inter simple sequence repeat) markers and 13 SSR (simple sequence repeat) markers. For the SSR markers were first made transferability analysis of primers from other species from Myrtaceae family. We tested 21 primer pairs, these 13 were successfully transferred to C. xanthocarpa. For molecular analyzes were used DNA from 20 trees per population. The ISSR primers generated 64 polymorphic loci, whereas the 13 primers (loci) generated 46 SSR alleles. The average genetic similarity between populations, estimated by Jaccard coefficient was 42% and 41%, with ISSR and SSR, respectively. These values indicate high genetic diversity among populations. The groupings of individuals and populations, made by UPGMA method with data from the two markers, based on different coefficients (Jaccard and Nei 1978), grouped individuals according to the population to which they belong, with the exception of the dendrogram based on similarity with the data SSR, only isolated individuals from the population A. The graphical distribution of individuals based on genetic relationships among them and dendrograms showed similar results indicating robustness in the analysis and reinforcing the structure of populations. The test performed with AMOVA based on ISSR data showed that most of the genetic variation is into populations (67%). Fst values (0.33) and Gst (0.26) show a high level of genetic differentiation between populations. Values found whit the SSR data refer heterozygotes deficiency considering all populations (Fit = 0.21) and also a high level of genetic differentiation between them (Fst = 0.19). Were also estimated with ISSR data the values of Ho = 0.42 (Shannon-Weaver) and He = 0.28 (Nei 1973). The estimated number of alleles (Na = 1.84) with ISSR was superior to the effective number of alleles (Ne = 1.47), being sufficient to maintain the current heterozygosity. With data from codominant marker was observed high percentage of polymorphic loci (P = 87.18%). The average observed heterozygosity with SSR markers among populations (Ho = 0.46) was very close to the expected (He = 0.47). With the SSR data were found five unique alleles in populations B and C and with data ISSR six exclusive loci were observed in the population B. The results indicate that the population B (connected with other fragments) shows greater genetic diversity, while the opposite occurs with the population A (isolated), and population C show intermediate values. The results also suggest that, although there is some diversity in populations of C. xanthocarpa, is occurring genetic differentiation between them, and loss of genetic variability in the population A, which is probably due to the isolation of populations conditioned by forest fragmentation.